Conceptual Analysis of Pro-Environmental Behavior: A Bibliometric Approach - ERYEŞİL, Kemalettin; ÖZTÜRK, Resul; ÖZTÜRK, Mehtap (International Journal of Contemporary Economics and Administrative Sciences, 2025)
This study presents an evaluation of the conceptual and historical evolution of the concept of pro-environmental behavior (PEB) through bibliometric analysis. PEB literature was evaluated through 4740 articles in the Web of Science (WOS) database published between 1981 and 2024. The development course of the PEB concept in the field was examined using performance and science mapping techniques and co-authorship, co-occurrence, citation, co-citation analysis using VOSviewer program. When the PEB literature was evaluated, it was determined that the concept was first expressed as conservation behavior and especially the term pro-environmental was used in different ways such as environmental friendly, environmentally responsible, sustainable, green, recycling. It was observed that the concept of PEB was first used in the literature in 1981. It has also been determined that the concept of PEB has been discussed within the framework of different theories, including the Norm Activation Model, the Theory of Planned Behavior and the Value-Belief-Norm Theory, and the theory that stands out in the literature is the Theory of Planned Behavior. However, there has been a gradual increase in the number of publications since 1981 and the literature has been in a rapid-growth phase in recent years. In this context, the concept of PEB is a popular phenomenon that has attracted attention in the literature in recent years. Over the years, the concept of PEB has evolved into consumer engagement, corporate greening, corporate social responsibility, emotional intelligence, employee green behavior, employee PEB, environmental commitment, environmental consciousness, environmental management, environmental passion, environmental performance, environmental sustainability, environmentally specific servant leadership, ethical leadership, environmental communication, environmental knowledge, environmental values, green human resource management, green leadership, green behavior, green attitudes, green culture, green values, organizational citizenship behavior, organizational culture, organizational commitment, organizational support, organizational identification, psychological green climate, innovation, intrinsic motivation, responsible leadership, spiritual leadership, transformational leadership. The relationship with these concepts was evaluated in terms of antecedents and consequences within the scope of the study and suggestions were made for future research directions.